2013
DOI: 10.1017/s1742170513000069
|View full text |Cite
|
Sign up to set email alerts
|

Organic agriculture in Iran: Farmers' barriers to and factors influencing adoption

Abstract: Organic agriculture is being promoted in Iran to address environmental problems resulted from the use of chemical materials in agriculture. Despite many advantages of organic agriculture, the results of several case studies show that its adoption rate is still very low among farmers. The purpose of this paper is to review previous studies that investigate the main factors influencing and challenges of adopting organic agriculture.The review included journal articles and conference papers from 2007 to 2012. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
45
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 13 publications
4
45
1
3
Order By: Relevance
“…This means that younger farmers have an inclination to accept organic farming as an innovative practice. One of the reasons behind this phenomenon is that younger farmers are more willing to take risks [10,27] and are interested in experimenting with new technology in comparison to older farmers [40]. However, the findings of the current study do not support the previous research conducted by Karki et al [20], Dunlap et al [21], Alzaidi et al [22], Dinpanah et al [23], and Ghane et al [24].…”
Section: Resultscontrasting
confidence: 92%
See 4 more Smart Citations
“…This means that younger farmers have an inclination to accept organic farming as an innovative practice. One of the reasons behind this phenomenon is that younger farmers are more willing to take risks [10,27] and are interested in experimenting with new technology in comparison to older farmers [40]. However, the findings of the current study do not support the previous research conducted by Karki et al [20], Dunlap et al [21], Alzaidi et al [22], Dinpanah et al [23], and Ghane et al [24].…”
Section: Resultscontrasting
confidence: 92%
“…The findings of this study are, however, consistent with that of Djokoto et al [40]. Some studies show that farmers who have engaged in agriculture over a long period of time are more interested in acquiring more experience about the successes and failures of the technology employed to turn out products [10,40]. For example, Isin et al [19], Jayawardana and Sherief [17], Oluwasusi [11], Adebayo and Oladele [34], Wheeler [31], and Chouichom and Yamao [30] indicated that farming experience has a positive effect on attitudes toward organic farming.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations